Cost/benefit analysis in the implementation of sustainable construction principles in a residential building - Martinho, Sérgio (2015)
The construction sector is one of the major contributors for the increase of pollution and environmental degradation. The uncontrolled increase on the consumption of natural resources, the way they are used and the high emissions they arise, are impelling the study and implementation of policies and procedures which ensure a sustainable future for construction and for the sustainability of the planet. The objective of this paper is to present the work devel-oped in order to assess and optimize the sustainability of a residential building at the design stage, through the application of a sustainability assessment tool, SBToolPT-H. A first evaluation was done, when conventional solutions were adopted. After this, a proposal was developed with several improvements in order to create a sustainable building that corresponds to the Portuguese best practices. This case study was developed taking into account the twenty-five sus-tainability indicators of the SBToolPT-H assessment system. Additionally, dynamic thermal simulation was used in order to support the optimization of the thermal performance and the indoor thermal comfort.